PELATIHAN SERVQUAL LEMBAGA PERKREDITAN DESA (LPD) - I Gede Putu Kawiana (UNHI Press, 2019)
Increasing the intensity of competition requires that every organization always pay attention to the dynamics of customer needs, wants and preferences and try to fulfill them in a way that is more effective and efficient compared to its competitors. The results of research on organizations that implement SERVQUAL (Service Quality) dimensions are proven as organizations that have sustainable competitiveness. LPD as a financial service institution should strive to provide quality services to its customers, but empirical data shows that in 2015 and 2016, around 28% of LPDs in Bali are still performing poorly. Performance is influenced by various factors, one of which is service quality. Filling in the gap, the SERVQUAL training is very necessary for the LPD. The purpose of this training is to motivate LPDs to intensively implement the SERVQUAL (Reliability, Tangiable, Responsiveness, Assurance, Emphaty) dimensions so that they become the LPD's organizational culture. Achieving these objectives is done through training with lecture methods, question and answer and demonstration. The implementation of this training went well and smoothly, and was able to motivate the management and LPD employees to implement the SERVQUALdimension.